Respuesta :
8x+8y=2
-) 8x+5y=1
——————
3y=1
y=1/3
8x+8(1/3)=2
24x+8=6
24x=-2
x=-1/12
(-1/12,1/3)
-) 8x+5y=1
——————
3y=1
y=1/3
8x+8(1/3)=2
24x+8=6
24x=-2
x=-1/12
(-1/12,1/3)
Answer:
Step-by-step explanation:
8x + 8y = 2 -------(1)
8x + 5y = 1 -------(2)
subtract equation (2) from equation (1)
The 8x will be eliminated, leaving us with;
3y = 1
Divide bothside of the equation by 3
y = 1/3
substituting y = 1/3 in equation (1)
8x + 8y = 2
8x + 8(1/3) = 2
8x + 8/3 = 2
subtract 8/3 from both-side
8x + 8/3 -8/3 = 2 -8/3
8x = 2 - 8/3
8x = 6 - 8 / 3
8x = - 2/3
Divide both-side of the equation by 8
8x / 8 = -2/3 ÷ 8
x = -2/3 × 1/8
x = -1 / 12